Born4Life: Creating and Supporting Meaningful, Authentic Intergenerational Experiences - Heslop, Kay; Caes, Line (Journal of Intergenerational relationships, 2025)
Intergenerational Practice, which brings two or more generations together for mutual benefit, is growing in popularity in the United Kingdom. While practices are well meaning, they are not always research informed. This critical evaluation research draws upon an evaluation of meaningful practice undertaken by Born4Life practitioners; a network of early years educators based in some Early Years settings across the UK, who are on an intergenerational journey. Through surveys, focus groups, and interviews, this research aimed to determine what an intentional, meaningful, and sustainable intergenerational community looks like and how such communities can be supported by identifying training and development requirements for the intergenerational team.